Psychoactive substances: consumption among workers from the mobile urgency care system - Márcia Astrês Fernandes; Mayrla Karen Rodrigues Mesquita; Danielle Machado Oliveira de Moura; Janaina dos Santos Francisco de Paula; Angela dos Santos Silva; Rosa Jordana Carvalho; Sandra Cristina Pillon (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To evaluate the consumption of psychoactive substances by health workers from the Mobile Urgency Care Service. Methods: A cross-sectional study conducted at a Public Health service located in a city in Piauí. Data collection took place from January to March 2019 by applying the following instruments in personal interviews: one with occupational, sociodemographic and economic characteristics; and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). The data were organized and processed in the Statistical Package for the Social Sciences (SPSS) software (version 19.0). Results: Of the 68 health professionals, 42 were male, with a mean age of 49.8 years old. Among them, 44 were married and 48 were Catholics. The most prevalent professional category was Nursing Technician, accounting for 46.2%. Among these workers, alcohol was the most used psychoactive substance (54 professionals), followed by tobacco consumption (25) and hypnotics (8). It is noted that tobacco was the substance most commonly used on a daily basis. Conclusion: Consumption of psychoactive substances among health professionals was evident and can be related to the pressure resulting from these positions. Attention is drawn to the importance of expanding this debate and addressing health workers' mental health.